Strategi Adaptasi Masyarakat Lokal Terhadap Bencana Longsor, Desa Giritirto, Kecamatan Purwosari, Kabupaten Gunungkidul - Syawallanny Hakim; Muhammad Hilmy Rahman; Putu Devi Ratih Wedaputri; Agnes Tasya Raja Gukguk; Istiqomah Wulandari; Noval Tri Nugroho; Lia Kusumawati (Jurnal Pendidikan Geografi Undiksha, 2026)
Giritirto Village, Purwosari Subdistrict, Gunungkidul Regency is an area with a high level of landslide vulnerability due to its karst hills and steep slopes. This study aims to describe the adaptation strategies of the local community to landslide disasters and their spatial distribution. The research used a descriptive qualitative approach with data collection through observation, interviews, and documentation. Informants were selected using the snowball sampling technique. The results show that the local community applies various forms of adaptation, both physical and social. Physical adaptations include the construction of retaining walls in residential areas, the application of terracing on agricultural land, and post-disaster residential relocation. Social adaptation is reflected in strong mutual cooperation during disaster response and recovery. Spatially, adaptation strategies are adjusted to land use, with retaining walls mainly built in residential areas and terracing applied on sloping agricultural land.